A Concise History of the Modern World - Woodruff, William. author. aut Link
X, 297 p.
Keywords: In an ever-shrinking world, the need for a global perspective in dealing with the modern world has become acute. This book attempts to provide such a perspective by investigating the major changes in geopolitics and world economy during the past 500 years. However compact, it enables us to understand the present unravelling of Communism and the growing challenge from Asia to Western Superiority. It is shown that in so many ways the problems of the contemporary world spring from the unprecedented era of western domination, which the non-western world is now trying to unlive.